2009
DOI: 10.1124/jpet.109.162933
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Chymase-Dependent Matrix Metalloproteinase-9 Activation on Indomethacin-Induced Small Intestinal Damages in Rats

Abstract: The side effects of nonsteroidal anti-inflammatory drugs (NSAIDs) include gastrointestinal damage not only in the stomach but also in the small intestine. Chymase converts promatrix metalloproteinase-9 to matrix metalloproteinase (MMP)-9, which plays an important role in NSAID-induced gastric damage, but it has been unclear whether chymase-dependent MMP-9 activation is involved in the NSAID-induced small intestinal damage. To clarify the involvement of chymase-dependent MMP-9 activation on NSAID-induced small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…We demonstrate chymase-mediated MMP-2 activation in the absence of cofactors including TIMP-2, MT1-MMP, or proteoglycan (PG)-GAG, indicating that chymase is sufficient to promote proteolytic MMP-2 activation. A role for chymase in MMP-9 processing and activation in animal models and Mcpt4 Ϫ/Ϫ mice has also been reported (25,27,47). We did not observe chymase-induced MMP-9 activation in our in vitro analyses.…”
Section: Discussionmentioning
confidence: 33%
“…We demonstrate chymase-mediated MMP-2 activation in the absence of cofactors including TIMP-2, MT1-MMP, or proteoglycan (PG)-GAG, indicating that chymase is sufficient to promote proteolytic MMP-2 activation. A role for chymase in MMP-9 processing and activation in animal models and Mcpt4 Ϫ/Ϫ mice has also been reported (25,27,47). We did not observe chymase-induced MMP-9 activation in our in vitro analyses.…”
Section: Discussionmentioning
confidence: 33%
“…After administration of indomethacin, MMP-9 activity was augmented, and the upregulation of MMP-9 induced intestinal barrier dysfunction and bacte- rial translocation (26). In the rat indomethacin-induced small intestinal injury model, a chymase inhibitor reduced MMP-9 activity in the small intestine, preventing small intestinal damage (27). Myeloperoxidase activity, which indicates neutrophil accumulation, was significantly increased in the small intestine after indomethacin administration, but its activity was significantly attenuated by treatment with a chymase inhibitor.…”
Section: Effects Of Inflammation-induced Organ Damagesmentioning
confidence: 99%
“…We recently demonstrated that non-steroidal anti-inflammatory drugs (NSAIDs)-induced small intestinal damage was involved in chymase-dependent MMP-9 formation (68). In these models, the disease activity index and histological damage score were significantly attenuated by chymase inhibitors via inhibition of chymase and MMP-9 activities (67,68).…”
Section: Target Diseases Other Than Cardiovascular Diseasesmentioning
confidence: 99%